The Influence of the Work Environment and Communication on Employee Performance of PT Pifi Indonesia Bandung - Belia Intan Fauzan; Karnowahadi - Karnowahadi; Rustono - Rustono (Politeknik Negeri Semarang, 2020)
The aim of this study is to analyze the effect of the Work Environment and Communication on Employee Performance at PT Pifi Indonesia Bandung both partially or simultaneously. This research uses quantitative research methods. The data collection technique in this study used a questionnaire and the sampling technique used was saturated sampling. The samples taken were 40 people who work at PT Pifi Indonesia Bandung. Sources of data in this study are primary data and secondary data. To analyze the data obtained, Multiple Linear Regression is used as statistical analysis along with descriptive analysis and classical assumption tests namely normality test, multicollinearity test, heteroscedasticity test, and linearity test. Hypothesis testing is processed using the SPSS 25 program (Statistical Package for Social Science). Based on the determinant coefficient, work environment and communication influenced employee performance by 26.7%. Meanwhile, the remaining 73.3% is explained by other variables not examined in this study. The t-test results indicate that the work environment and communication has partial positive and significant effect on employee performance.